A Performance Review of Grass Swales Channel in Malaysia - ABDUL SALIM, MUHAMMAD IZZAT IMAN; Noor Aliza, (Recent Trends in Civil Engineering and Built Environment, 2021)
Grass swales is a series of vegetated open channel that are designed specifically to treat and attenuate stormwater runoff for a specified water quantity volume. The aim of this research is to study the hydraulics characteristics of grass swales and to study the flow attenuation and the flow conveyance of swale. Studies showed that grass swales are very efficient in stormwater quality control by reducing volume and peak flowrate. The previous studies the performance of grass swales in term of stormwater quantity control have been analyzed from the article and journal. The method that used including Mean-Section Method to evaluate the flow discharge and Manning’s equation to determine the hydraulic roughness. Rational method has been used to calculate the peak discharge, peak flow and volume runoff reduction to determine the performance of swales as stormwater quantity control. Based on the finding, grass swale in Malaysia has volume reduction in the range of 19.4% to 69.8% and peak flow reduction of 28.9% to 55.9%. At the end of the study, will be able to find out the hydraulic characteristics of grass swale and the flow attenuation and conveyance of swale and whether the application of grass swale suitable to be applied as one of the best management practices (BMP) in mitigating flash flood in Malaysia.